FAKTOR- FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA BPKAD KABUPATEN NGANJUK) - Praharsiwi Dewanti, Wika (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of thiis study is that to analyze how the implementation of the governmennt acccounting standards, iinternal control, and humann resourcee competence on the qualiity of local government financiial reporting at BPKAD. Furthermore, this researrch adopts a quantitatiive approoach using causality investigation research methods. Data analysis is also with traditional hypothesis testing, determinant testing (R2), and hypothesis testing. What is new in the this study is the diifference bettween the research variables and the location of the study. The resultss of this the study are to show SAP can have a significant influence on the qualityy of local government financiial reporting. Partial internal control also has a significant impact on the qualiity of local goverrnment financiial reporting Hr competence that can have a signiificant impact also on the quuality of locall government finanncial reportiing. Furthermore, SAP, innternal controll and HR competence affect the quaality of financial reporting of the regiional governmment of BPKAD Nganjuk Regency.